(untitled) (Texas Journal of Agriculture and Biological Sciences, 2026)
The article presents data on the influence of different application rates of various phosphorus fertilizers on the growth and development of winter wheat. According to research, phosphorus fertilizers had a significant impact on the growth and development of soft winter wheat on light-gray soils in the Kashkadarya region.